FORMATION OF PROFESSIONALLY IMPORTANT QUALITIES AS A BASIC COMPONENT OF TRAINING AND SOCIALIZATION OF FUTURE SPECIALISTS IN THE ECONOMIC INDUSTRY - Chernenko Nаtaliia (Educological discourse, 2021)
The article outlines a range of issues regarding the need to form professionally important qualities as an integral part of the basic competencies of future economists, which is impossible without general educational competence as one of the main and most important conditions for achieving professionalism in economics, competitiveness in the labor market. The professional qualities of specialists in various fields are considered and the main blocks of qualities for the future economist are determined. The content of each of the blocks is highlighted and the essence of professionally important qualities (PO) and general components for the economic direction of training are revealed, as the variety of qualities is determined by the specifics of work, working conditions and job responsibilities. The problems of formation of professionally important qualities in the process of training economic specialists in universities, as well as the main purpose of vocational education - is to create conditions for development and self-realization of each individual, the formation of a generation capable of lifelong learning. The issue of effective professional socialization is revealed, which provides for the formation of a specialist in the economic profile of the basic system of values ​​and norms of behavior of the professional community, which form the basis of social behavior in the professional sphere and are structural elements of competence. The requirements of the modern labor market are analyzed: the close relationship between the rapid pace of development and the aging of professional knowledge and skills, which involves maintaining a high level of professional mobility of the economic specialist throughout life. The content of the concepts "criteria" and "indicators" of the effectiveness of the process of formation of professionally important qualities is considered. Psychological regularities and modern, concrete practical approaches to the organization of the educational process in professional training are revealed. Methods and techniques that increase the interest of future professionals in their own education and self-education, continuous professional growth, self-improvement, self-development and self-realization are identified. Also, these main active methods of teaching the andragogical approach, which increase the interest of future economists in continuous professional development, contribute to their effective adaptation, socialization and competitiveness in the labor market.